COVID-19 in Health-Care Workers: A Living Systematic Review and Meta-Analysis of Prevalence, Risk Factors, Clinical Characteristics, and Outcomes - Gómez-Ochoa, Sergio Alejandro; Franco, Oscar H; Rojas, Lyda Z; Raguindin, Peter Francis; Roa-Díaz, Zayne Milena; Wyssmann, Beatrice Minder; Guevara, Sandra Lucrecia Romero; Echeverría, Luis Eduardo; Glisic, Marija; Muka, Taulant (American journal of epidemiology, 2021)
Health-care workers (HCWs) are at the frontline of response to coronavirus disease 2019 (COVID-19), being at a higher risk of acquiring the disease and, subsequently, exposing patients and others. Searches of 8 bibliographic databases were performed to systematically review the evidence on the prevalence, risk factors, clinical characteristics, and prognosis of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection among HCWs. A total of 97 studies (all published in 2020) met the inclusion criteria. The estimated prevalence of SARS-CoV-2 infection from HCWs' samples, using reverse transcription-polymerase chain reaction and the presence of antibodies, was 11% (95% confidence interval (CI): 7, 15) and 7% (95% CI: 4, 11), respectively. The most frequently affected personnel were nurses (48%, 95% CI: 41, 56), whereas most of the COVID-19-positive medical personnel were working in hospital nonemergency wards during screening (43%, 95% CI: 28, 59). Anosmia, fever, and myalgia were the only symptoms associated with HCW SARS-CoV-2 positivity. Among HCWs positive for COVID-19 by reverse transcription-polymerase chain reaction, 40% (95% CI: 17, 65) were asymptomatic at time of diagnosis. Finally, severe clinical complications developed in 5% (95% CI: 3, 8) of the COVID-19-positive HCWs, and 0.5% (95% CI: 0.02, 1.3) died. Health-care workers suffer a significant burden from COVID-19, with those working in hospital nonemergency wards and nurses being the most commonly infected personnel.